2023
DOI: 10.1177/08927057231174217
|View full text |Cite
|
Sign up to set email alerts
|

Spring-in behavior of woven carbon fiber/polycarbonate thermoplastic composites

Abstract: The spring-in behavior of woven carbon fiber/polycarbonate thermoplastic composite is investigated by both the experiment and simulation ways. These thermoplastic composite plates are thermoformed into V-shaped structures, and the final bending angle is measured after demolding. In the finite element simulation to describe the thermoforming and spring-in behavior of the composite, the discrete approach is adopted to simulate the behavior of woven carbon fabric and combined with a resin model. The results from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Han et al [42] indicated significant spring-in values from 2.087 • to 3.431 • for carbon fiber-reinforced PPS laminate thermoformed into a 92-degree V-shape as the forming temperature of 320 • C and the tool temperature changed from 80 • C to 230 • C. For symmetrical laminates, the lay-up sequence, either [[(0/90)/(±45)] 2 ] S or [[(±45)/(0/90)] 2 ] S , had little effect on the spring-in value. Hwang et al [43] investigated the angle deviation of woven carbon fiber/polycarbonate composites after thermoforming and found that the spring-in angle was around 2.60 • for a 60 • V-shape and around 1.72 • for a 90 • V-shape for [(±45)] 6 blanks. The [(0/90)] 6 blank had a slightly higher spring-in angle than the previous blanks.…”
Section: Parameter Effects From Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Han et al [42] indicated significant spring-in values from 2.087 • to 3.431 • for carbon fiber-reinforced PPS laminate thermoformed into a 92-degree V-shape as the forming temperature of 320 • C and the tool temperature changed from 80 • C to 230 • C. For symmetrical laminates, the lay-up sequence, either [[(0/90)/(±45)] 2 ] S or [[(±45)/(0/90)] 2 ] S , had little effect on the spring-in value. Hwang et al [43] investigated the angle deviation of woven carbon fiber/polycarbonate composites after thermoforming and found that the spring-in angle was around 2.60 • for a 60 • V-shape and around 1.72 • for a 90 • V-shape for [(±45)] 6 blanks. The [(0/90)] 6 blank had a slightly higher spring-in angle than the previous blanks.…”
Section: Parameter Effects From Experimentsmentioning
confidence: 99%
“…For symmetrical laminates, the lay-up sequence, either or , had little effect on the spring-in value. Hwang et al [ 43 ] investigated the angle deviation of woven carbon fiber/polycarbonate composites after thermoforming and found that the spring-in angle was around 2.60° for a 60° V-shape and around 1.72° for a 90° V-shape for blanks. The blank had a slightly higher spring-in angle than the previous blanks.…”
Section: Parameter Effects From Experimentsmentioning
confidence: 99%